Study of the electrical Power quality in the common connection point between a 7.8 kWp PV system and a low-voltage network (2018)
(Eng) An experimental 1,000 kWh/month PV solar system was connected to a low-voltage network at the Universidad de Ibagué, Colombia. In this work, we present the findings about the electrical voltage issues in the common connection point. The characterization of the low-voltage network was based on the NTC 5001standard, including aspects such as voltage imbalance, intermittency, short and long-term flicker, and harmonics. The maximum energy production was 850 kWh /month, equal to the 72.65% of the total installed capacity. In this condition, the minimum voltage measure - ments evidenced a 2 % increase from the previous value, the voltage imbalance was 3.5 to 70 percent lower, and the voltage harmonics (TDH) increased 7, 0.8 and 3 percent in the phases U 1 , U 2 and U 3 , respectively. Current harmonics did not show significant increases in lines U 2 and U 3 , line U1 recorded an increase of 22%, but there were no significant variations in the short and long-term flicker, notches and interruptions. Regarding the electrical power, the active and reactive components increased 58 and 42%, respectively, and the thermographic study indicated a 7.5 percent increas - ing temperature after the installation of the experimental PV system. This experience aims to be a reference project in the implementation of the Act 1715 of the Colombian government to promote solar systems.